Acute ST‐elevation myocardial infarction due to septic embolism: A case report and review of management options. Issue 6 (12th February 2015) - Singh, Maninder; Mishra, Abhishek; Kaluski, Edo
Abstract : Acute ST‐elevation myocardial (STEMI) infarction due to septic embolism is rare and management strategies differ from those applied to atherothrombotic STEMI. A 70‐year‐old male with aortic valve endocarditis and persistent bacteremia developed acute inferior wall STEMI due to septic embolism. Due to inferior STEMI accompanied by hemodynamic instability, coronary angiography and primary PCI (stenting) to a totally occluded right coronary artery (RCA) was performed. Despite excellent immediate angiographic results and hemodynamic stabilization, repeat angiogram two weeks later showed mycotic aneurysms at the site of stent placement. Patient later suffered from intracranial hemorrhage and splenic infarct and had worsening aortic regurgitation, prompting surgical aortic valve replacement with bypass of the RCA. Despite aggressive medical, interventional and surgical management, he expired four weeks after the surgery. Selection of an optimal revascularization strategy in this scenario is unclear with a potential harm from standard therapies. We have reviewed prior reports and summarized results in a tabular form. © 2015 Wiley Periodicals, Inc.